2022
DOI: 10.1111/dme.14781
|View full text |Cite
|
Sign up to set email alerts
|

Toward a better understanding of transition from paediatric to adult care in type 1 diabetes: A qualitative study of adolescents

Abstract: Aims Type 1 diabetes is associated with significant morbidity, with an increasing risk of acute diabetes‐related complications in adolescence and emerging adulthood. Purposeful transition from paediatric to adult‐oriented care could mitigate this risk but is often lacking. Detailed understanding of the perspectives of adolescents in their final year of paediatric care is essential to inform delivery of transition care programs. Methods We conducted semi‐structured interviews with adolescents (aged 17 years) wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…We recently conducted a qualitative study focusing on the perspectives of adolescents in their final year of paediatric care. We found that participants with a longer diabetes duration felt more confident in their ability to manage their condition 13 . On the other hand, previous studies in younger adolescents (ages 11–17 years) have shown that shorter diabetes duration is associated with better adherence to diabetes care activities and better glycaemic control 6,14 .…”
Section: Introductionmentioning
confidence: 56%
“…We recently conducted a qualitative study focusing on the perspectives of adolescents in their final year of paediatric care. We found that participants with a longer diabetes duration felt more confident in their ability to manage their condition 13 . On the other hand, previous studies in younger adolescents (ages 11–17 years) have shown that shorter diabetes duration is associated with better adherence to diabetes care activities and better glycaemic control 6,14 .…”
Section: Introductionmentioning
confidence: 56%
“…10 12 15 Previous research examining young adults' experiences have reported several factors contributing to transition challenges, including feeling pushed out of paediatric care, 16 inadequate preparation, [16][17][18] challenges with accessing adult care, 19 desire to transfer earlier or later, 18 reluctance to end relationship with the paediatric team 12 20 and feeling discouraged by briefer visits and directive communication styles in the adult care setting. 19 However, these studies were conducted pretransfer, [21][22][23] in a private payer healthcare setting 15 24-27 had small-sample sizes when examining post-transfer experiences, 28 29 and/ or included a large age range (ie, with many participants being several years to a decade post-transfer). 25 30 We recently examined the experiences and perceptions of adolescents during the pretransfer period (ie, final year of paediatric T1D care) and identified the need for transition programmes to support disease-specific self-management and healthcare system navigation.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…25 30 We recently examined the experiences and perceptions of adolescents during the pretransfer period (ie, final year of paediatric T1D care) and identified the need for transition programmes to support disease-specific self-management and healthcare system navigation. 23 Our current study sought to explore the transition care perceptions of emerging adults living with T1D after their transfer to adult care. The exploration of perceptions of this same cohort after transfer helps complete the narrative on how young adults living with T1D perceive the transition from paediatric to adult care and how this process could be improved.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 99%
“…Data from a self-selecting group in the U.S. has documented this widely recognized pattern ( 1 ), and their later report showed that, despite the increased use of technology, glycemia in people aged 15 to 18 years had deteriorated further ( 2 ). It is commonly assumed that poor communication and changes in continuity and support during the transfer from pediatric to adult services at the age of 16 to 18 years are important reasons ( 3 ) for more severe hyperglycemia at this stage of life. However, the influence of growth-related hormonal change on insulin requirements is also recognized ( 4 ) as a key factor in age-related changes.…”
Section: Introductionmentioning
confidence: 99%